Antibacterial and Antioxidant Capacities of Tanjong (Mimusops elengi L.) Leaf Extract - Piboonpol, Gornganok; Hounkong, Kruawan; Khunchana, Nattanicha; Santiparadon, Manutsanun; Somsap, On-Anong (Princess of Naradhiwas University Journal, 2019)
The objective of this research was to study antibacterial activity, phytochemical. The objective of this research was to study antibacterial activity, phytochemical screening, and antioxidant activityof Tanjong leaf extract. Antibacterial activity was determined by agar well diffusion method. The result showed that Tanjong leaf extract exhibited against gram positive bacteria such as Bacillis cereus ATCC 11778, Micrococcus luteus TISTR884, as well as the methicillin-resistant Staphylococcus aureus 142 (MRSA142) andStaphylococcus aureus TISTR517 with the inhibition zone 21.7, 21.3, 29.0 and 21.8 mm, respectively. However, gram negative bacteria were resistant to Tanjong leaf extract. The MIC value of the Tanjong leaf extract gave 9.38 mg/ml with B. cereus ATCC 11778 and MIC value were given equally: 18.75 mg/ml with M. luteus TISTR884, MRSA142 and S. aureus TISTR517. The MBC value to inhibit B. cereus ATCC 11778, M. luteus TISTR884andS. aureus TISTR517 were 300 mg/ml and MBC value for MRSA142 was 600 mg/ml. Phytochemical screening test showed that Tanjong leaf extract contained flavonoids, phenols, and saponins.The Tanjong leaf extract showed antioxidant activity at 3.2 µg ascorbic acid/g fresh weights and the IC50 at 23.35 µg/ml. Moreover, the total flavonoid content was 0.8 mg Quercetin/g fresh weights and phenolic content was 0.72 mg gallic acid/ g fresh weights.